UNITED NATIONS OFFICE ON DRUGS AND CRIME (UNODC) MELALUI PROGRAM GLO. ACT ASIA DAN TIMUR TENGAH DALAM MENGATASI PERDAGANGAN MANUSIA DAN PENYELUNDUPAN MIGRAN - Feby Anggrela; Robi Sugara (Indonesian Association for International Relations, 2024)
This study aims to analyze the eradication of human trafficking and migrant smuggling cases by UNODC through the GLO.ACT Asia and Middle East program in Afghanistan, Iraq, Iran, and Pakistan. This study was formulated by looking at the facts of program implementation in each country and then analyzed using the concepts of International Organizations, Trafficking in Persons, and Smuggling of Migrants with qualitative methods through interviews and literature studies. This study found that the GLO.ACT program has attempted to develop strategies and policies, legislative assistance, capacity building, regional and transregional cooperation, and protection and assistance to victims of these cases in the four countries. However, the GLO.ACT program intervention in target countries has different progress and challenges depending on the cooperation of each government and the ability of UNODC and its partners in managing the program